SISTEM PENGOLAHAN NILAI UNTUK KURIKULUM PAUD BERBASIS DESKTOP DENGAN MODEL WATERFALL - Muksan SAN Junaidi (SIMETRIS, 2021)
The data processing of Al-Amin's Play Group student scores is still done manually, namely by handwriting on student assessment booksheets, this takes a long time and is not effective. The development of the number of students that increases from year to year requires accuracy in providing assessments without any mistakes and repetition of the same data. The purpose of this research is to design and make student assessment applications with object-oriented programming in the Al-Amin Play Group. Using the Waterfall model System Development Life Cycle (SDLC) method, the design based on the Unified Modeling Language (UML) and the Java Netbeans 8.2 programming language MySQL database. The research data includes student data, student attendance every semester from 2018 to 2019. The final result of the research is an object-oriented student assessment system that can be accessed through a laptop, personal computer (PC) device which is expected to help the foundation to facilitate data collection and processing of value data students and can see the progress of students in each semester at the Al-Amin Play Group in Kedewan Village. The system test results were declared feasible in terms of functionality, amounting to 97.9% in black box testing.